Wine tourism and COVID-19: impacts and responses from the perspective of wine route’s wineries. - Cerezo-Medina, Alfonso; Peláez-Verdet, Antonio; Gaspar-González, Ana Isabel; Martín-Rojo, Inmaculada Concepción (Uhu Publicaciones, 2023)
Wine tourism is a subsector of gastronomic tourism that, according to the World Tourism Organisation, has been increasingly in demand among visitors worldwide. The Serranía de Ronda has an outstanding wine-growing tradition, but the region has had to deal with one of the most significant challenges in recent times: the coronavirus disease-19 pandemic. This study analyzed the crisis’s impacts on wine tourism along the Ronda and Malaga Wine Route, winemakers’ perceptions of these effects, and how wineries reacted. Exploratory mixed-methods research was carried out using a combination of primary and secondary sources. The results were compared to other studies that have also sought to analyse wineries’ recovery strategies associated with the pandemic. The findings have practical implications that can help wine tourism providers improve their resilience during future pandemics.
Keywords: Vino - Cata; Turismo; Serranía de Ronda (Málaga) - Descripción y viajes; COVID-19; Serranía de Ronda; Wine tourism; Online tastings; Wine routes